De-Lovely - Winkler, Irwin; Cocks, Jay.; Cowan, Rob.; Winkler, Charles; Porter, Cole, 1891-1964.; Kline, Kevin; Judd, Ashley; Pryce, Jonathan; McNally, Kevin; Nelson, Sandra, 1962-; Williams, Robbie; Lemar; et al. (Santa Monica, California : MGM Home Entertainment, 2004)
A musical portrait of American composer Cole Porter. The film imagines Porter looking back on his life as a stage show, with past memories taking shape as numbers in an elaborate and elegant musical accompanied by his songs. His personal history is illustrated by these performances, especially the complicated relationship with his wife, wealthy socialite Linda Lee Porter, who is shown as being the main inspiration for his work despite his extramarital affairs.
Special features: optional audio commentary by director Irwin Wnkler and Kevin Kline; optional audio commentary by director Irwin Winkler and writer Jay Cocks; "Making of De-Lovely" featurette (26 min.); "Music of De-Lovely" featurette (16 min.); "Anatomy of a scene: Be a clown" featurette (6 min.); "Anatomy of a scene: Love for sale" short (4 min.); deleted scenes (14 min.); original theatrical trailer (3 min.); soundtrack TV spot (1 min.)
Music & lyrics by Cole Porter ; music arranged and produced by Stephen Endelman ; director of photography, Tony Pierce-Roberts ; editor, Julie Monroe.
Kevin Kline, Ashley Judd, Jonathan Pryce, Kevin McNally, Sandra Nelson, Allan Corduner, Peter Polycarpou, Keith Allen, James Wilby.
Musical performers: Robbie Williams, Lemar, Elvis Costello, Alanis Morrisette, John Barrowman, Caroline O'Connor, Sheryl Crow, Mick Hucknall, Diana Krall, Vivian Green, Lara Fabian, Mario Frangoulis, Natalie Cole.
MPAA rating: PG-13; for sexual content.
DVD, region 1; Dolby Digital 5.1 surround, stereo surround.
Keywords: Porter, Cole, -- 1891-1964 -- Drama; Porter, Cole, -- 1891-1964 -- Teatro; Musical films -- Drama. -- United States; Husband and wife -- Drama; Closeted gays -- Drama; Compositores (Música) -- Teatro. -- Estados Unidos; Musicals -- Feature; Feature films; Musical films; Biographical films; Films for the hearing impaired